Efforts to Utilize Organic Waste Through Compost Making Training in Batang Duku Village - Dadang Mashur; Meizatul Lidiana Azmi; Susi Hanasty; Mikael Louis Simbolon; Retno Putri Wigatiningrum; Harun; M. Irvan Repal; Mery Fitriani; Riena Asni Artia. S; Nanda Oktavia; Liya Tri Wahyuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Compost plays a role in improving soil structure which is useful for increasing plant growth. The purpose of conducting training on making compost is to educate and conduct training for farmer groups in the Batang Duku Village community which is useful in implementing it for the gardens of each farmer group, so that community needs can be met with the presence of compost. The method used in this community service activity is in the form of a question and answer lecture discussion for farmer groups by conducting training. The results of the activity evaluation obtained an increase in the participants' knowledge of the activities before and after the training, resulting in increased public interest in using compost compared to using chemical fertilizers.